Single dose oral diclofenac for acute postoperative pain in adults. - Derry, P; Derry, S; Moore, R; McQuay, H (2009)
BACKGROUND: Diclofenac is a non-steroidal anti-inflammatory drug (NSAID), available as a potassium salt (immediate-release) or sodium salt (delayed-release). This review updates an earlier review published in The Cochrane Database of Systematic Reviews (Issue 2, 2004) on 'Single dose oral diclofenac for postoperative pain'. OBJECTIVES: To assess single dose oral diclofenac for the treatment of acute postoperative pain. SEARCH STRATEGY: Cochrane CENTRAL, MEDLINE, EMBASE, Biological Abstracts, the Oxford Pain Relief Database, and reference lists of articles were searched; last search December 2008. SELECTION CRITERIA: Randomised, double-blind, placebo-controlled clinical trials of single dose, oral diclofenac (sodium or potassium) for acute postoperative pain in adults. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed studies for inclusion and quality, and extracted data. The area under the pain relief versus time curve was used to derive the proportion of participants with at least 50% pain relief over 4 to 6 hours, using validated equations. Relative benefit (risk) and number needed to treat to benefit (NNT) were calculated. Information on adverse events, time to remedication, and participants needing additional analgesia was also collected. MAIN RESULTS: Fifteen studies (eight additional studies) with 1512 participants more than doubled the information available at each dose. Overall 50% to 60% of participants experienced at least 50% pain relief over 4 to 6 hours at any dose with diclofenac, compared to 10 to 20% with placebo, giving NNTs of about 2.5 for doses of 25 mg to 100 mg (similar to earlier review); no dose response was demonstrated. At 50 mg and 100 mg, NNTs for diclofenac potassium (2.1 (1.8 to 2.4) and 1.9 (1.7 to 2.2)) were significantly lower (better) than for diclofenac sodium (6.7 (4.2 to 17) and 4.5 (3.2 to 7.7)). The median time to use of rescue medication was 2 hours for placebo, 4.3 hours for diclofenac 50 mg and 4.9 hours for diclofenac 100 mg. Adverse events were reported at a similar rate to placebo, with no serious events. AUTHORS' CONCLUSIONS: Oral diclofenac is an effective single-dose treatment for moderate to severe postoperative pain. Significantly more participants experienced at least 50% pain relief over 4 to 6 hours with diclofenac potassium than with diclofenac sodium. There was no significant difference between diclofenac and placebo in the incidence of adverse events.